Benefits of physical exercise on cognition and glial white matter pathology in a mouse model of vascular cognitive impairment and dementia. Issue 9 (10th March 2020) - Trigiani, Lianne J.; Lacalle‐Aurioles, María; Bourourou, Miled; Li, Lijun; Greenhalgh, Andrew D.; Zarruk, Juan G.; David, Samuel; Fehlings, Michael G.; Hamel, Edith
Abstract: White matter (WM) pathology is a clinically predictive feature of vascular cognitive impairment and dementia (VCID). Mice overexpressing transforming growth factor‐β1 (TGF) with an underlying cerebrovascular pathology when fed a high cholesterol diet (HCD) develop cognitive deficits (VCID mice) that we recently found could be prevented by physical exercise (EX). Here, we further investigated cognitive and WM pathology in VCID mice and examined the cellular substrates of the protective effects of moderate aerobic EX focusing on WM alterations. Six groups were studied: Wild‐type (WT) and TGF mice ( n = 20–24/group) fed standard lab chow or a 2% HCD, with two HCD‐fed groups given concurrent access to running wheels. HCD had a significant negative effect in TGF mice that was prevented by EX on working and object recognition memory, the latter also altered in WT HCD mice. Whisker‐evoked increases in cerebral blood flow (CBF) were reduced in HCD‐fed mice, deficits that were countered by EX, and baseline WM CBF was similarly affected. VCID mice displayed WM functional deficits characterized by lower compound action potential amplitude not found in EX groups. Moreover, there was an increased number of collapsing capillaries, galectin‐3‐expressing microglial cells, as well as a reduced number of oligodendrocytes in the WM of VCID mice; all of which were prevented by EX. Our findings indicate that a compromised cerebral circulation precedes reduced WM vascularization, enhanced WM inflammation and impaired oligodendrogenesis that all likely account for the increased susceptibility to memory impairments in VCID mice, which can be prevented by EX. Main Points: A compromised cerebral circulation increases susceptibility to anatomical and functional white matter changes that develop alongside cognitive deficits when challenged with a high cholesterol diet; preventable by a translational regimen of exercise.